Unravelling the relationship between perceived values-congruence with organizational change readiness: A moderated mediation model - Deng, Jinzhao; Cheng, Zhihui; Qi, Siqi; Deng, Rich (Frontiers in Psychology, 2023)
Employees’ organizational change readiness is crucial for the successful implementation of organizational change. Integrating the self-categorization theory and social information processing theory, we propose a moderated mediation model to investigate how and when perceived values-congruence with their organizations, supervisors, and workgroups (PVC-O, PVC-S, and PVS-G) helps stimulate the employees’ organizational change readiness. We collected a valid sample of 252 employees from six companies that underwent organizational changes. We found that PVC-O, PVC-S, and PVS-G are all positively related to perceived insider status (PIS), which further promotes their readiness for organizational change. Moreover, high quality of change communication not only strengthens the positive effect of employees’ PVC-O and PVC-G (except for PVC-S) on PIS but also strengthens the indirect effects of PIS. Finally, we also discussed the theoretical contributions and practical implications of the present study.